(untitled) (Bioagro, 2025)
The bacterium Azospirillum brasilense has been studied for being associated with the stimulation of plant growth by production of auxins, especially indole acetic acid, in addition to the biological fixation of nitrogen. Genome analysis is used to generate a genome fingerprint matrix and with them build a tree to distinguish the differences between species of this genus. To carry out this analysis, it was carried out with the virtual genomic fingerprinting method using the VAMPhyRE program. Probes were designed to detect 19 nucleotides and with the results obtained, a genomic fingerprint matrix was generated from which a genomic tree of minimal evolution was built, which revealed the phylogenomic relationships between the species of the genus, highlighting that the Brazilian species A is separated in a clade perfectly differentiated from the other species of the group. Likewise, the analysis allowed us to detect that the A brasilense genome is composed of 19,284 genes, which is equivalent to 16 % of the genes annotated and make up the core genome of the strains analyzed. Likewise, 27 % are moderately conserved genes. This is evidence of the great genomic variability that the species presents. In addition, a graph of the genome of the species was generated. Also, using the PROKKA program and the virtual genomic fingerprinting method, a matrix of distances and a phylogenomic tree of minimal evolution were generated, without roots, in radial shape showing that all A. brasilense strains are housed in the same clade and separated from the other species of this genus.